Acquisition of English Vocabulary for Children Aged 3 Years Through Youtube Social Media and Habit Forming - Hernalia Citra Dewi; Dwinesa Anggraeni (research, training and philanthropy institution Natural Aceh, 2023)
Acquisition of a second language means a human process of acquiring the ability to generate, capture, and use words unconsciously to communicate. This study aims to find out what vocabulary three-year-old children receive from their habit of watching YouTube videos and their parents' habits at home. This study uses a qualitative method with descriptive explanations. Data collection techniques were carried out through observation and interviews. The results of this study found that subjects of second language skills in English were evident from their understanding of the questions and videos that they had watched repeatedly and the formation of their parents' habits. Mastery of a second language was also seen in the subject's ability to name food, fruits, and animals and to name simple verbs and verb phrases in English. The study results showed that the issue acquired 46 English vocabulary